2020
DOI: 10.7759/cureus.7945
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Revision Adenoidectomy Among Pediatric Patients at King Abdulaziz University Hospital in Saudi Arabia

Abstract: BackgroundAdenoidectomy is the most commonly performed pediatric operation worldwide and one of the most frequent otorhinolaryngological procedures. It is a safe procedure with a low risk of complications. However, after a successful adenoidectomy, few patients experience symptoms of nasal obstruction, suggestive of adenoid regrowth. Because of various risk factors, patients require a revision adenoidectomy. This study aimed to determine the incidence of revision adenoidectomy at King Abdulaziz University Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In our study, we also found that children presenting with clinical features of recurrent tonsillitis carried a higher odd of having revision adenoidectomy ( P = 0.006). This is similar to findings by Alsharif et al [ 28 ] This may be due to the effects of factors such as allergy, infection, and acid reflux on the pharyngeal mucosa. [ 8 ] Studies have demonstrated a high incidence of gastric acid reflux among children undergoing adenoidectomy, and this is found to be associated with mucosal edema and inflammation in the pharynx, leading to adenoid and tonsil hyperplasia/hypertrophy, and hence a risk for recurrent tonsillitis and revision adenoidectomy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, we also found that children presenting with clinical features of recurrent tonsillitis carried a higher odd of having revision adenoidectomy ( P = 0.006). This is similar to findings by Alsharif et al [ 28 ] This may be due to the effects of factors such as allergy, infection, and acid reflux on the pharyngeal mucosa. [ 8 ] Studies have demonstrated a high incidence of gastric acid reflux among children undergoing adenoidectomy, and this is found to be associated with mucosal edema and inflammation in the pharynx, leading to adenoid and tonsil hyperplasia/hypertrophy, and hence a risk for recurrent tonsillitis and revision adenoidectomy.…”
Section: Discussionsupporting
confidence: 91%
“…[ 8 ] Studies have demonstrated a high incidence of gastric acid reflux among children undergoing adenoidectomy, and this is found to be associated with mucosal edema and inflammation in the pharynx, leading to adenoid and tonsil hyperplasia/hypertrophy, and hence a risk for recurrent tonsillitis and revision adenoidectomy. [ 8 28 29 ] However, as we could not ascertain the presence or absence of acid reflux in the cohort, it is thus difficult to establish a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, adenoidectomy is the definitive method for managing AH worldwide, but it may be associated with a variety of complications, including hemorrhage, infections, palate dysfunction and the risks associated with general anesthesia. In addition, there is still a possibility of recurrence after surgery [ 6 ]. It is estimated that 20–30% children with OSAS could have symptoms returned after surgery, about 50% of which were due to adenotonsillar regeneration.…”
Section: Discussionmentioning
confidence: 99%